Answer:
f(-3) = g(-3)
Step-by-step explanation:
Remember points on the graph get their location from the x-axis (horizontal) and y-axis (vertical).
In function notation, "f(x)" means when "x" is the value in the brackets, what the value of "y" will be.
First option for example: f(-3) = g(4)
<em>Value of "y" for f(x) when x = -3:</em>
On the blue line, when x = -3, y = -4.
<em>Value of "y" for g(x) when x = 4:</em>
On the red line, when x = 4, y = -3.
<u>Therefore</u>:
f(-3) = g(4)
-4 = -3 <= This is false.
In the third option: f(-3) = g(-3)
<em>On f(x) blue, when x = -3: </em>y = -4
<em>On g(x) red, when x = -3: </em>y = -4
<u>Therefore</u>:
f(-3) = g(-3)
-4 = -4 <= This is true.
Solve for x. Isolate the x. Note the equal sign. What you do to one side, you do to the other. Do the opposite of PEMDAS.
First, multiply 3 to both sides
6(3) = ((x + 2)/3)(3)
18 = x + 2
Finally, isolate the x. Subtract 2 from both sides
18 (-2) = x + 2 (-2)
x = 18 - 2
x = 16
16 is your answer for x
hope this helps
Answer:
I and IV are congruent and I I and III are congruent.
Step-by-step explanation:
Congruent figures must have the same shape and measurements. Hope this helps.
A = the number before x^2 = 3
b = the number before x = 5
To find the axis of symmetry: -b/2a
x = -5/6
Answer:
Option D. (x + 4)(x + 1)
Step-by-step explanation:
From the question given above, the following data were obtained:
C = (6x + 2) L
D = (3x² + 6x + 9) L
Also, we were told that half of container C is full and one third of container D is full. Thus the volume of liquid in each container can be obtained as follow:
Volume in C = ½C
Volume in C = ½(6x + 2)
Volume in C = (3x + 1) L
Volume in D = ⅓D
Volume in D = ⅓(3x² + 6x + 9)
Volume in D = (x² + 2x + 3) L
Finally, we shall determine the total volume of liquid in the two containers. This can be obtained as follow:
Volume in C = (3x + 1) L
Volume in D = (x² + 2x + 3) L
Total volume =?
Total volume = Volume in C + Volume in D
Total volume = (3x + 1) + (x² + 2x + 3)
= 3x + 1 + x² + 2x + 3
= x² + 5x + 4
Factorise
x² + 5x + 4
x² + x + 4x + 4
x(x + 1) + 4(x + 1)
(x + 4)(x + 1)
Thus, the total volume of liquid in the two containers is (x + 4)(x + 1) L.